2020
DOI: 10.1096/fj.202000405rr
|View full text |Cite
|
Sign up to set email alerts
|

CCN6 regulates mitochondrial respiratory complex assembly and activity

Abstract: Cellular communication network factor 6 (CCN6) mutations are linked with Progressive Pseudo Rheumatoid Dysplasia (PPRD) a debilitating musculoskeletal disorder. The function of CCN6 and the mechanism of PPRD pathogenesis remain unclear. Accordingly, we focused on the functional characterization of CCN6 and CCN6 mutants. Using size exclusion chromatography and native polyacrylamide gel electrophoresis we demonstrated that CCN6 is present as a component of the mitochondrial respiratory complex in human chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
(122 reference statements)
2
20
0
Order By: Relevance
“…30 CCN6 maintains the structure and function of mitochondria and regulates ROS production. 9,10 As such, our findings provide an important pavement in the search for the mechanisms by which CCN6 plays a role in NASH.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…30 CCN6 maintains the structure and function of mitochondria and regulates ROS production. 9,10 As such, our findings provide an important pavement in the search for the mechanisms by which CCN6 plays a role in NASH.…”
Section: Discussionmentioning
confidence: 60%
“…Increased accumulation of FFA in hepatocytes leads to enhanced mitochondrial β‐oxidation and increased production of ROS, 29 whilst endogenous antioxidant systems become less efficient in the steatotic liver 30 . CCN6 maintains the structure and function of mitochondria and regulates ROS production 9,10 . As such, our findings provide an important pavement in the search for the mechanisms by which CCN6 plays a role in NASH.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…14 However, recent functional studies demonstrated a role of CCN6 in the mitochondrial respiratory complex assembly/activity and ATP production. 15 Hence, mutations in CCN6 result in mitochondrial defects and deprived cell survival. Sengupta et al 16 used a zebrafish model to study functional effects of CCN6 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Gel filtration chromatography of total nuclear lysate was performed following previously documented procedures 31,33 . The total nuclear lysate was prepared from cultured C28/I2 cells following the protocol described before.…”
Section: Methodsmentioning
confidence: 99%